2017
DOI: 10.1093/mnrasl/slx133
|View full text |Cite
|
Sign up to set email alerts
|

The relation between galaxy morphology and colour in the EAGLE simulation

Abstract: We investigate the relation between kinematic morphology, intrinsic colour and stellar mass of galaxies in the EAGLE cosmological hydrodynamical simulation. We calculate the intrinsic u − r colours and measure the fraction of kinetic energy invested in ordered corotation of 3562 galaxies at z = 0 with stellar masses larger than 10 10 M . We perform a visual inspection of gri-composite images and find that our kinematic morphology correlates strongly with visual morphology. EAGLE produces a galaxy population fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
121
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(134 citation statements)
references
References 53 publications
13
121
0
Order By: Relevance
“…(x) We find that a threshold value of κ co = 0.4 (Correa et al 2017) roughly corresponds to our F = 0 threshold separating bulge-, from disc-dominated systems. However, we notice that the optical and kinematic criteria do not select the same galaxy populations.…”
Section: Summary and Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…(x) We find that a threshold value of κ co = 0.4 (Correa et al 2017) roughly corresponds to our F = 0 threshold separating bulge-, from disc-dominated systems. However, we notice that the optical and kinematic criteria do not select the same galaxy populations.…”
Section: Summary and Discussionsupporting
confidence: 55%
“…Scannapieco et al 2008). In the case of eagle, variations of these metrics have been studied by Correa et al (2017Correa et al ( , 2019, Clauwens et al (2018), Trayford et al (2019) and Tissera et al (2019).…”
Section: Dependence On Rotationmentioning
confidence: 99%
“…P07 require an apparent axis ratio b/a ≤ 0.6 and usable Hα rotation curve, which they find not to significantly bias the admitted galaxy population in colour or concentration. We therefore do not make a morphology cut on the EAGLE galaxies in our fiducial analysis, although we have checked that our results change at no more than the ∼ 1σ level -and our qualitative conclusions remain unchanged -when only including galaxies with a substantial fraction of their kinetic energy in ordered corotation (κ co ≥ 0.4; Correa et al 2017). We compare the EAGLE results with two semi-empirical models, denoted "SHAM" and "SHAM+MMW" as in Section 1.…”
Section: Data Models and Statisticsmentioning
confidence: 86%
“…6 we show the 3D Sérsic index (measured from the 3D stellar mass distributions) and the kinematic bulge-to-total, B/T, ratio 1 as a function of stellar mass for galaxies at z = 0 that have not suffered mergers, and had at least one dry or wet merger. This figure shows that no-merger galaxies have much lower Sérsic indices and B/T ratios than galaxies that 1 B/T ≡ 1 − κ co , where κ co is the ratio of kinetic energy invested in ordered rotation calculated using only star particles that follow the direction of rotation of the galaxy (see Correa et al 2017 for more details). We also analysed the Abadi et al (2003) and Sales et al (2010) .…”
Section: The Net Effect Of Galaxy Mergers Seen At Z =mentioning
confidence: 99%
“…Recently, using cosmological hydrodynamical simulations, Sparre & Springel (2017) found that galaxy remnants of major mergers evolve into star-forming disc galaxies unless sufficiently strong feedback is present to prevent the disc regrowth. This feedback is an essential mechanism in the new generation of cosmological hydrodynamical simulations, such as EAGLE (Schaye et al 2015), Illustris (Vogelsberger et al 2014) and HORIZON-AGN (Dubois et al 2014), and most likely plays a major role in reproducing the morphological diversity seen in galaxies (Dubois et al 2016;Correa et al 2017).…”
mentioning
confidence: 99%